HERV-W ENV antigenemia and correlation of increased anti-SARS-CoV-2 immunoglobulin levels with post-COVID-19 symptoms - Giménez-Orenga, Karen; Pierquin, Justine; Brunel, Joanna; Charvet, Benjamin; Martín-Martínez, Eva; Perron, Hervé; Oltra, Elisa (Frontiers in Immunology, 2022)
Due to the wide scope and persistence of COVID-19´s pandemic, long COVID-19 represents a post-viral syndrome of unprecedented dimensions. SARS-CoV-2, in line with other infectious agents, has the capacity to activate dormant human endogenous retroviral sequences ancestrally integrated in human genomes (HERVs). This activation was shown to relate to aggravated COVID-19 patient´s symptom severity. Despite our limited understanding of how HERVs are turned off upon infection clearance, or how HERVs mediate long-term effects when their transcription remains aberrantly on, the participation of these elements in neurologic disease, such as multiple sclerosis, is already settling the basis for effective therapeutic solutions. These observations support an urgent need to identify the mechanisms that lead to HERV expression with SARS-CoV-2 infection, on the one hand, and to answer whether persistent HERV expression exists in long COVID-19, on the other. The present study shows, for the first time, that the HERV-W ENV protein can still be actively expressed long after SARS-CoV-2 infection is resolved in long COVID-19 patients. Moreover, increased anti-SARS-CoV-2 immunoglobulins in long COVID-19, particularly high anti-SARS-CoV-2 immunoglobulin levels of the E isotype (IgE), seem to strongly correlate with deteriorated patient physical function (r=-0.8057, p<0.01). These results indicate that HERV-W ENV antigenemia and anti-SARS-CoV-2 IgE serology should be further studied to better characterize long COVID-19 pathogenic drivers potentially differing in subsets of patients with various symptoms. They also point out that such biomarkers may serve to design therapeutic options for precision medicine in long COVID-19.